Writing in the disciplines: Comparison of critical stance qualities in literary analyses by university students writing in L1 and L2 contexts - Ndoricimpa, Clément; Barad, Dilip P. (Indonesian Journal of Applied Linguistics, 2024)
Construing critical stance in disciplinary writing is an important expectation. It is important because studies have shown a correlation between critical thinking and high score on writing. Therefore, this study compared the qualities of critical stance in literary analyses by university students in an outer circle country and by university students in an inner circle country. The data consisted of high-graded assignments by university students at seven universities in Gujarat state in India and successful assignments from British Academic Written English (BAWE) corpus. To analyze the data, appraisal theory- a subset of systemic functional linguistics- was employed. The results showed that university students in India predominantly construed in their literary analyses a descriptive and empty ethical stance. In contrast, university students in UK construed in their literary analyses a critic voice marked by caution, discourse alignment. Further, the results indicated that the descriptive and empty ethical stance was marked by the use of linguistic resources of affect and judgement in higher frequency while the critic voice in BAWE corpus was marked by the use of the linguistic resources of appreciation and engagement in higher frequency. These results have far-reaching implications for writing research and for assessing and teaching disciplinary writing in outer circle countries. They show evidence of the differences in the qualities of critical stance that students writing in L1 and L2 context construe in their disciplinary writing. They also give evidence of the differences in the assessment of students’ writing in L1 and L2 context.